The Effect Of Capital, Financing, And Operational Efficiency On Profitability Through Financing Risk Mediation In Sharia BPR - Parjiyanto, Parjiyanto; Lutfi, Lutfi (UNIVED Press, 2026)
This study investigates the impact of capital adequacy (CAR), financing (FDR), and operational efficiency (BOPO) on profitability (ROA), with financing risk (NPF) as a mediating variable, in Islamic Rural Banks (BPRS) in East Java during 2019–2023. Using a quantitative approach with panel data regression on 24 BPRS over five years of observation (N = 120), model selection tests (Chow, Hausman, and Lagrange Multiplier) identified the Random Effect Model as the most appropriate estimation method. Mediation analysis was conducted using the Baron & Kenny causal step approach. The findings show that financing risk (NPF) and operational efficiency (BOPO) negatively and significantly affect profitability, while capital adequacy (CAR) and financing (FDR) exert no significant effect. Importantly, NPF demonstrates a full mediating role in the relationship between FDR and ROA, suggesting that financing can enhance profitability only when supported by effective risk management. This study underscores the necessity for Islamic banks to strengthen adaptive risk management and operational efficiency to achieve sustainable profitability.